Gastrostomy tube feeding in children with cerebral palsy: a prospective, longitudinal study. - Sullivan, P; Juszczak, E; Bachlet, A; Lambert, B; Vernon-Roberts, A; Grant, H; Eltumi, M; McLean, L; Alder, N; Thomas, A (2005)
We report a longitudinal, prospective, multicentre cohort study designed to measure the outcomes of gastrostomy tube feeding in children with cerebral palsy (CP). Fifty-seven children with CP (28 females, 29 males; median age 4y 4mo, range 5mo to 17y 3mo) were assessed before gastrostomy placement, and at 6 and 12 months afterwards. Three-quarters of the children enrolled (43 of 57) had spastic quadriplegia; other diagnoses included mixed CP (6 of 57), hemiplegia (3 of 57), undiagnosed severe neurological impairment (3 of 57), ataxia (1 of 57), and extrapyramidal disorder (1 of 57). Only 7 of 57 (12%) could sit independently, and only 3 of 57 (5%) could walk unaided. Outcome measures included growth/anthropometry, nutritional intake, general health, and complications of gastrostomy feeding. At baseline, half of the children were more than 38D below the average weight for their age and sex when compared with the standards for typically-developing children. Weight increased substantially over the study period; the median weight z score increased from -3 before gastrostomy placement to -2.2 at 6 months and -1.6 at 12 months. Almost all parents reported a significant improvement in their child's health after this intervention and a significant reduction in time spent feeding. Statistically significant and clinically important increases in weight gain and subcutaneous fat deposition were noted. Serious complications were rare, with no evidence of an increase in respiratory complications.